(untitled) (International Journal of Communication Systems and Network Technologies, 2018)
Aphenomena of hiding any information are known as data hiding. For hiding data a number of techniques are used.Hiding of data can be done withan audio, video,text and image.Inserting data in other data are a way of stenography.Mainly, in a digital image we hide data.It is equally mandatory to provide security with data hiding because data aretransmitted over the network.There are many robust methods for encryption of images as per requirement. This paper provides a detailed survey of various techniques available for RDH.